EKSISTENSI KEPOLISIAN SEKTOR DALAM MEWUJUDKAN KEAMANAN DAN KETERTIBAN MASYARAKAT DI NAGARI KURANJI HILIR DAN KOTO TINGGI KABUPATEN PADANG PARIAMAN - Kasman, Kasman (UNES Law Review, 2019)
According to Article 13 of Law No. 2 of 2002, the main task of the National Police is to maintain public security and order, uphold the law and provide protection, protection and service to the community. Placement in the lurah / village and nagari is the Existence of Sector Police Implementation in realizing the security and order of the people of Nagari Kuranji Hilir and Koto Tinggi Kabupaten Padang Pariaman is the Implementation of Kapolri Regulation Number 3 of 2015. The approach model implemented by Sector Police is a model of community policing arrogance ( Community Policing). The formulation of the problem in the study is, first, How the Existence of the Inner Sector Police Realizes the Security and Order of the Nagari Kuranji Hilir Community and Koto Tinggi Kabupaten Padang Pariaman? Padang Pariaman? what three efforts should be corrected in the Existence of the Sector Police in Realizing the Security and Order of the Nagari Kuranji Hilir Community and Koto Tinggi Kabupaten Padang Pariaman? This research is a legal research wicth analysis descriptive specification. The approach used is a normative Juridical approach supported by an empirical Juridical approach. The data used are secondary data and primary data collected through library studies and field studies. The data is then analyzed qualitatively and presented in the form of descriptive qualitative. The conclusions of the study are, First, the Existence of Sector Police in Realizing the Security and Order of Nagari Kuranji Hilir and Koto Tinggi Communities Sungai Limau District, Padang Pariaman Regency is carried by the Existence of Bhabinkamtibmas by adopting local wisdom, pre-emptive efforts, pam swakarsa development, forming community policing, FKPM and Pokdar Kamtibmas, Do Problem Solving through the ADR pathway; Second, the constraints in the implementation faced by the Sector Police in Realizing the Security and Order of the Nagari Kuranji Hilir Community and Koto Tinggi Sungai Limau Subdistrict, Padang Pariaman Regency, are citizens' legal awareness which tends to view a win lose solution, area, demography and geography have hills, rivers and lurahs. ratio ratio 1: 3,000. and third Efforts to overcome obstacles to implementation Existence of Sector Police in Realizing Security and Order The people of Nagari Kuranji Hilir and Koto Tinggi of Kabupaten Padang Pariaman are Polri publishing Smart Books on Bhabinkamtibmas, Increasing Knowledge, Bhabinkamtibmas such as Training and vocational education.